Baltic *aušklējas m. & *aušklējā f. "bleak" - Blažek, Václav (Baltistica, 2018)
The present contribution is devoted to the Baltic designation of the fish "bleak / Alburnus alburnus" in Lithuanian, Latvian, Prussian toponymy, and in traces of Baltic substrata in North Russian dialects and in Mari from the upper Volga basin. They are studied from the point of view of phonetic history and word formation. Any etymological attempts must be realized together with Slavic counterparts of this Baltic ichthyonym. On the basis of existing etymologies a new solution is proposed, explaining the fish-name with help of one of characteristic features of this fish, golden slime on its scales. The new etymology demonstrates their common origin in the compound *au̯s- & *klēi̯o/ā- *"gold-slimed" = "fish characterized by its golden slime". This fish-name would further solidify the original Indo-European term for "gold", directly preserved in the Baltic and Italic branches, in another apophonic formation also in Tocharian, but, until now, quite unattested in Slavic.
Keywords: Baltic; Slavic; Mari; ichthyonym; toponym; substratum; compound; etymology; gold